Nutrient Composition and Sensory Properties of Biscuit from Mushroom-Wheat Composite Flours - , M. Bello, M. O. Oluwamukomi, V. N. Enujiugha (Archives of Current Research International, 2018)
The nutrient composition and the acceptability of biscuit from composite flours of wheat and Pleurotus sajur-caju (PSC) mushroom were evaluated. Pleurotus sajur-caju (PSC) mushroom was dried, processed into flour and used to substitute wheat flour as composite flour. The composite flour was at 0, 5, 10, 20 and 30% level of mushroom addition, the resulting mixtures were then used to produce biscuits. The proximate composition, minerals, physical (spread ratio, weight, thickness) and sensory properties of the composite biscuit were evaluated. The protein content increased from 13.04% in the control (100% WF) to a range of 13.41% - 15.55%. in the biscuits; crude fibre increased from 2.10 to 2.16 - 2.93 %.; ash content increased from 1.52% to a range of 1.87 - 3.85%, while crude fat and carbohydrate reduced from 21.71 to 19.05 - 20.58% and 61.63 to 58.62 - 61.58% respectively. As the ratio of mushroom level increased, the mean, thickness, diameter, weight as well as the spread ratio increased. The result of the mineral analysis revealed that the sodium and potassium were the predominant mineral elements in the biscuit samples and the mineral composition increases with level of mushroom addition. There was no significant difference in the overall acceptability of the control (100% WF) and 5% mushroom substitution samples. This shows the viability of producing nutritious biscuits with desirable nutritional qualities from mushroom-wheat up to 10% mushroom substitution level.